Dogma 2002-2021 : familiar / extraño : familiar / unfamiliar. - Poveda, Cristina (Madrid : El Croquis Editorial, 2021)
Bilbao, Tatiana ; Aureli, Pier Vittorio ; Tattara, Martino ; Bhatia, Neeraj
boek
Keywords: Dogma